Hydrocortisone administration for reducing post-traumatic stress symptoms: A systematic review and meta-analysis. (April 2021) - Kothgassner, Oswald D.; Pellegrini, Marie; Goreis, Andreas; Giordano, Vito; Edobor, Joy; Fischer, Susanne; Plener, Paul L.; Huscsava, Mercedes M.
Abstract: Background: Post-traumatic stress disorder (PTSD) is a debilitating disorder that is often accompanied by alterations in the hypothalamic-pituitary (HPA) axis. While there is abundant evidence for the efficacy of psychological therapies in reducing post-traumatic stress symptoms, barely anything is known about pharmacological interventions. Given the role of the HPA axis in the pathophysiology of PTSD, the aim of this study was to provide the first meta-analysis of Hydrocortisone as a potential treatment for this condition. Method: A systematic review of randomized-controlled trials (RCTs) was conducted to investigate the efficacy of hydrocortisone in the prevention and curative treatment of post-traumatic stress symptoms. This study was pre-registered with the OSF (doi:10.17605/OSF.IO/GJAZF). Findings: Eight studies (9 effect sizes) covering 362 participants met our inclusion criteria. We found that Hydrocortisone as compared to placebo significantly reduced PTSD symptoms ( d = 0.96, 95% Cl 0.22–1.69 p = 0.011) and PTSD incidence (logRR = 0.85, 95% CI 1.12–1.59, p = 0.023). Subgroup analyses revealed a significant effect of Hydrocortisone when it was administered in a preventative context ( d = 1.50; 95%CI 0.30–2.69, p  = 0.014), but not when it was administered in a curative context ( d = 0.28; 95%CI −0.11 to 0.66, p  = 0.161). Conclusion: Hydrocortisone appears to be a promising and efficient low-cost medication for the prevention of PTSD. However, the small number of included studies and their limited methodological quality emphasize the need for further rigorous studies in this field. Highlights: Hydrocortisone showed promising effects to prevent post-traumatic stress symptoms. Hydrocortisone effects were found in preventive therapies, not in patients with an existing PTSD. Intravenous administration yielded a large effect in reducing post-traumatic stress symptoms. Hydrocortisone might be a useful and low-cost supplement to psychological therapy for PTSD.